Model Tabligh Salmanitb.com dalam Menyajikan Berita Islami - M. Ambang Fajar Hilman; Sitty Sumijati; Bahrudin Bahrudin (Department of Islamic Communication and Broadcasting, Faculty of Dakwah and Communication, UIN Sunan Gunung Djati Bandung, 2016)
This study describes the application model tabligh SalmanITB.com in presenting Islamic news. This research is a qualitative-descriptive research using case study method. The theory used is journalistic theory or news presentation consisting of coverage, writing, and dissemination of news with materials. After the research, it was found that the application of Tabligh SalmanITB.com in presenting Islamic news refers to three main processes (coverage, writing, and dissemination of news) as the theory of news presentation, evidenced by sampling news on the materials needed. Based on this finding, it can be concluded that SalmanITB.com's tabligh model in presenting Islamic news has been in accordance with the rules of the news presentation process. Tulisan ini mendeskripsikan model penerapan tabligh SalmanITB.com dalam menyajikan berita-berita Islami. Penelitian ini merupakan penelitian kualitatif-deskriptif menggunakan metode studi kasus. Teori yang digunakan adalah teori jurnalistik atau penyajian berita yang terdiri dari peliputan, penulisan, dan penyebarluasan berita. Penerapan tabligh SalmanITB.com dalam menyajikan berita-berita islami mengacu pada tiga proses utama (peliputan, penulisan, dan penyebarluasan berita) sebagaimana teori penyajian berita, dibuktikan dengan pengambilan sampel berita pada materi-materi yang dibutuhkan. Berdasarkan penemuan ini dapat disimpulkan bahwa model tabligh SalmanITB.com dalam menyajikan berita islami telah sesuai dengan aturan proses penyajian berita.